Promoting Nature of Science Understanding for Elementary School through Joyful Learning Strategy - Subuh Anggoro; Ari Widodo; Ng Khar Thoe; Nelson Cyril (The Indonesian Institute of Science and Technology Research, 2022)
Most of students, teachers and preservice teachers has not understood the nature of science by. Even though the teacher's understanding of the nature of science that properly and mastery will affect students' the ability to do open mind, imagination, and creativity. The purpose of this study is to implement a learning plan that develops open mind, imagination, and creativity using Joyful Learning Strategy. The mixed methods used and the participants were 223 preservice elementary teachers (41 males and 182 females) and 32 elementary school students (10 males and 22 females). The questionnaire of NOS and joyful learning observation worksheet were validated. Data analysis used descriptive with percentage and qualitative descriptive. The results showed many preservice elementary teachers have misunderstanding about science as product, process, attitude and social interaction. Through joyful learning can develop students' students' the ability to do open mind, imagination, and creativity. Some suggestions are Joyful Learning with integrated learning will be able to generate students' the ability to do open mind, imagination, and creativity when the teacher understands the nature of science properly. The learning environment of the classroom and school facilities and non-physical interaction between teachers and students become important factors of joyful learning success.